2007
DOI: 10.1002/jbm.a.31310
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous and crystalline polyetheretherketone: Mechanical properties and tissue reactions during a 3‐year follow‐up

Abstract: The study was aimed to test the mechanical strength, structural stability, and tissue reactions of optically amorphous and crystalline polyetheretherketone (PEEK) plates during a 3-year follow-up in vivo and in vitro. The injection-moulded PEEK plates were implanted to the dorsal subcutis of 12 sheep, which were sacrificed at 6-156 weeks. Thereafter, the plates were subjected to tensile tests, and levels of crystallinity were assessed by differential scanning calorimetry (DSC). Histological evaluation was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 13 publications
(25 reference statements)
2
79
0
1
Order By: Relevance
“…Interest in improving PEEK's osseointegration has accelerated in recent years after numerous reports have described its inability in smooth form to facilitate bone apposition [9,23,25,34,51]. Reasons why this interest persists (as opposed to abandoning PEEK altogether) are often attributed to the other qualities of PEEK that make it favorable in orthopaedic and spinal applications, mainly its radiolucency, MRI compatibility, high strength, and fatigue resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in improving PEEK's osseointegration has accelerated in recent years after numerous reports have described its inability in smooth form to facilitate bone apposition [9,23,25,34,51]. Reasons why this interest persists (as opposed to abandoning PEEK altogether) are often attributed to the other qualities of PEEK that make it favorable in orthopaedic and spinal applications, mainly its radiolucency, MRI compatibility, high strength, and fatigue resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, attributable in part to PEEK's relatively inert and hydrophobic surface, recent evidence has demonstrated that smooth PEEK can exhibit poor osseointegration [9,25] and fibrous capsule formation around the implant [23,34]. Lack of bone-implant contact can induce micromotion and inflammation that leads to fibrous layer thickening, osteolysis, and implant loosening [2,13,29,37,48].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its excellent mechanical properties, PEEK is chemically inert and resistant to sterilization. [1][2][3][4][5][6][7][8] These features may be of great advantage for a biomaterial. PEEK has been used in orthopedic applications for decades and in the late 1990s, became widely used as a substitute for metal implants in spinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Conrad et al [26] demonstrated that this increased mould temperature may also increase the compressive modulus, yield strength and strain of the traditional PEEK/HA composites. Working temperatures greater than 380℃ have been shown to reduce crystallinity, which is known to be beneficial for ductility and toughness [27,28] , with no adverse effect on biocompatibility in vivo [27] . Given the positive effects described on both shear viscosity and mechanical properties of the resulting PEEK samples, a mould temperature of 400℃ was selected for this study.…”
Section: Resultsmentioning
confidence: 99%